Support for the Death Penalty in Cases of Rape and Sexual Assault: Variation between Victim Age Categories - Dierenfeldt, Rick (International journal of offender therapy and comparative criminology, 2021)
Research exploring attitudes toward the death penalty is common in the field of criminal justice. Additionally, a substantial body of literature has examined public perceptions of sex offenders and punishment in the U.S. Unfortunately, few studies have sought to examine perceptions of the death penalty in relation to sexual offending. This study contributes to the literature by examining perceptions of the college students at a mid-sized university in the Southeastern United States as they relate to support for the death penalty in cases of sexual assault across victim age categories. Findings suggest that respondent perceptions are shaped by biological sex, political affiliation, college major, fear of crime, and parents’ level of education, and these relationships are uniform across victim age categories. Further, support for the death penalty appears inversely related with victim age.